Використання мережі інтернет, як необхідна складова модернізації та вдосконалення політичної системи суспільства - Гаража, Р. Ю. (ХНУРЕ, 2021)
The paper considers the possible impact of Internet technologies on the system of political institutions, as well as trends in the use of Internet communications in politics. It is emphasized that Internet communication is an integral part of the political process, performing the functions of information exchange between actors of political interaction, political institutions and civil society organizations. The advantages and disadvantages of using Internet technologies as a tool of political communication are identified.
Keywords: філософія; мережа інтернет